Global Sourcing of Information Technology and Business Processes 4th International Workshop, Global Sourcing 2010, Zermatt, Switzerland, March 22-25, 2010, Revised Selected Papers - Oshri, Ilan; Kotlarsky, Julia (Lecture Notes in Business Information Processing, 2010)
This edited book is intended for use by students, academics and practitioners who take interest in outsourcing and offshoring of information technology and business pr- esses. The book offers a review of the key topics in outsourcing and offshoring, po- lated with practical frameworks that serve as a tool kit to students and managers. The range of topics covered here is wide and diverse. The sourcing models available to client firms are discussed in great depth and the decision-making processes and c- siderations regarding the sourcing model and sourcing settings are examined. Vendor capabilities as well as client capabilities are studied in depth and links are offered to the various sourcing models. Issues pertaining to knowledge and expertise are also discussed throughout the book. Last but not least, the book examines current and - ture trends in outsourcing and offshoring, paying particular attention to the role that CIOs will play in shaping their sourcing strategies. The book is based on a vast empirical base brought together through years of - tensive research by the leading researchers of outsourcing and offshoring. June 2010 Ilan Oshri Julia Kotlarsky Organization Global Sourcing Workshop is an annual gathering of academics and practitioners. Program Committee Workshop Chair Leslie Willcocks (London School of Economics, London, UK) Workshop Committee Julia Kotlarsky (Warwick Business School, Coventry, UK) Ilan Oshri (Rotterdam School of Management, Rotterdam, The Netherlands) Joseph Rottman (St. Louis University, St.